Solution-Focused Approach as a Means of Enhancing Teacher Professionalism - Katarzyna Justyna Klimkowska (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Abstract Introduction Teachers' development programmes focus on the achievement of profession-related and pedagogical competence, as well as on the shaping of professional conduct and culture. Teachers' work and their personal and professional goals are affected by how they perceive themselves as persons and as professionals, and also by how they see their students and the teaching environment. Research Aim This article aims to present SFA philosophy and explore its implications for the growth of teachers' professionalism, irrespective of its national or international contexts. The article unveils how to use SFA to make it advantageous for teachers' professional growth. The article explores the following topics: 1)     SFA as a worldview and a methodology of explaining human experience useful for building developmental relations; 2)     SFA as an inventory of educational and developmental techniques useful for contemporary classrooms;   3)     SFA as an inventory of self-development activities in constructing teachers' life and professional success. Evidence-based Facts Professionalism of the teachers is approached from different perspectives - as highly qualified professionals, as a set of given attitudes towards all participants of the education process, or as a space for teachers' professional growth that relates to development and mastering the profession. The main aim of the Solution-Focused Approach (SFA) is looking for solutions in the preferred/desired future, which allows one to find solutions to a present problem. Summary Solution-Focused Approach  is a tool that can be used to empower the acquisition of personal and professional competences by teachers. It can enrich university curricula and teacher training programmes.